2009
DOI: 10.1007/s11295-009-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

QTL influencing growth and wood properties in Eucalyptus globulus

Abstract: Regions of the genome affecting physical and chemical wood properties (quantitative trait loci (QTL)), as well as growth, were identified using a clonally replicated, outbred F 2 family (112 genotypes, each with two ramets) of Eucalyptus globulus, planted in a field trial in north-west Tasmania. Traits studied were growth (assessed by stem diameter), wood density, cellulose content, pulp yield and lignin content. These traits are important in breeding for pulpwood, and will be important in breeding for carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 38 publications
6
47
2
Order By: Relevance
“…Furthermore, the clustering of QTLs controlling height and basal diameter has been observed in the same mapping population of E. ulmoides (Li et al, 2014c). In most cases, no clear patterns among phenotypic correlations have been found to coincide with the co-locating QTLs (Tsarouhas et al, 2002;Gailing, 2008;Freeman et al, 2009;Thumma et al, 2010;Li et al, 2014c). In the present study, we found that 16 QTLs were unique to specific traits (Figure 2).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Furthermore, the clustering of QTLs controlling height and basal diameter has been observed in the same mapping population of E. ulmoides (Li et al, 2014c). In most cases, no clear patterns among phenotypic correlations have been found to coincide with the co-locating QTLs (Tsarouhas et al, 2002;Gailing, 2008;Freeman et al, 2009;Thumma et al, 2010;Li et al, 2014c). In the present study, we found that 16 QTLs were unique to specific traits (Figure 2).…”
Section: Discussionsupporting
confidence: 72%
“…Previous QTL studies on main crops have frequently detected regions of the genome that contain clusters of QTLs for highly correlative traits (Zeng et al, 2009;Avia et al, 2013;Bian et al, 2013). Clusters of QTLs were also observed for growth traits and various leaf traits in poplar (Bradshaw and Stettler, 1995;Wu et al, 1997), for wood properties and growth traits in the genus Eucalyptus (Verhaegen et al, 1997;Freeman et al, 2009;Thumma et al, 2010), for growth traits in Salix (Tsarouhas et al, 2002;Ronnberg-Wastljung et al, 2005), for leaf morphological characters in European beech (Scalfi et al, 2004) and oak (Gailing, 2008;Gailing et al, 2013), and for chemical compositions in peach (Eduardo et al, 2013) and oil palm (Montoya et al, 2013). Furthermore, the clustering of QTLs controlling height and basal diameter has been observed in the same mapping population of E. ulmoides (Li et al, 2014c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly applied to gene sequences and gene products (Fitch, 2000;Petsko, 2001). Homology of QTL has been classically defined as QTL that map to the same position in different populations or species (for example, see Freeman et al, 2009). In lineage-specific QTL mapping, we can subdivided homology into 'orthology of QTL' , as QTLs that share common ancestry (share the same mutational event of an ancestor), and 'paralogy of QTL' , as QTLs that have different mutations in the same region of the genetic map, but which arise independently.…”
Section: Corolla Lengthmentioning
confidence: 99%
“…However, only few studies in most widely cultivated species of Eucalyptus have analyzed CGs underlying wood quality traits using QTL approaches (Freeman et al, 2009;Thumma et al, 2010;Gion et al, 2000Gion et al, , 2011. The use of already well-established variable markers present in CGs for wood quality is an interesting approach for mapping purposes and functional diversity studies.…”
mentioning
confidence: 99%